Master techniques in upper and lower airway management 2026-02-16T12:07:59+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Popescu, Wanda M.; Rosenblatt, William H. (Wolters Kluwer Heath, 2015)

(untitled)
This book provides comprehensive coverage of upper and lower airway problems relating to anesthesia administered during surgery and their management from evaluation through preexisting conditions. Coverage includes otolaryngology and maxillofacial procedures, nasal intubation, tracheostomy, pediatric patients, the at-risk cervical spine, interventional pulmonology, lung isolation, airway surgery, congenital abnormalities of the lower airway, and lung transplantation